Pengaruh Penerapan Ekonomi Sirkular dan Inovasi Digital terhadap Efesiensi Operasional UMKM - Tiara Ananta Sinaga; Muhammad Yafiz; Purnama Ramadani Silalahi (Jurnal Simki Economic, 2026)
Demands for efficiency and competitiveness of MSMEs are increasing in the face of a dynamic business environment, limited resources, and the acceleration of digital transformation. The circular economy and digitalization are seen as two key strategies with the potential to sustainably improve MSME operational performance. Based on these issues, this study aims to analyze the impact of the implementation of a circular economy and digitalization innovation on the operational efficiency of micro, small, and medium enterprises (MSMEs). This study uses a quantitative approach with multiple linear regression analysis. The research sample involved 100 MSMEs located in North Sumatra Province and was determined through a purposive sampling technique. Data were collected by distributing structured questionnaires to MSMEs, then analyzed using SPSS statistical software to test the partial and simultaneous effects between research variables. The findings indicate that the implementation of a circular economy has a positive and significant effect on MSME operational efficiency. In addition, digitalization innovation has also been shown to have a positive and significant impact on operational efficiency. This study confirms that the implementation of a circular economy and digitalization innovation are strategic factors in improving the operational efficiency of MSMEs in North Sumatra Province. Therefore, MSMEs and stakeholders are expected to encourage the sustainable adoption of these two strategies to improve their performance and competitiveness.